2018
DOI: 10.3389/fpsyt.2018.00615
|View full text |Cite
|
Sign up to set email alerts
|

Moral Emotions and Social Economic Games in Paranoia

Abstract: Impaired social cognitive processes are putative psychological mechanisms implicated in the formation and maintenance of paranoid beliefs. Paranoia denotes unfounded fears about the hostile intentions of others and is prevalent in a significant proportion of the general population. We investigated social cognition in healthy participants selectively recruited to have a broad occurrence of paranoid thinking (n = 89). Participants completed a novel computerized task of moral emotions and two social economic exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 68 publications
1
16
0
1
Order By: Relevance
“…Neuroimaging 42 studies have observed increased presynaptic dopamine leading up to (21) and 43 during (22) the development of psychotic symptoms, suggesting aberrant 44 dopaminergic transmission as crucial in sensitisation (23). Experimental data support 45 the sensitisation of cognitive and affective processes that manifests as a 'jumping to 46 conclusions' probabilistic reasoning bias (12,24), high initial mistrust (25,26) and 47 more threatening or negatively valanced responses following heightened social 48 arousal (27,28). 49…”
Section: Background 22mentioning
confidence: 98%
“…Neuroimaging 42 studies have observed increased presynaptic dopamine leading up to (21) and 43 during (22) the development of psychotic symptoms, suggesting aberrant 44 dopaminergic transmission as crucial in sensitisation (23). Experimental data support 45 the sensitisation of cognitive and affective processes that manifests as a 'jumping to 46 conclusions' probabilistic reasoning bias (12,24), high initial mistrust (25,26) and 47 more threatening or negatively valanced responses following heightened social 48 arousal (27,28). 49…”
Section: Background 22mentioning
confidence: 98%
“…By using trait measurements and a task that elicited emotions, however, we were able to uncover a pattern reminiscent of depression: more guilt and shame in the highly empathic under serotonin depletion. Indeed, this task has already been used to detect possible latent vulnerabilities in a healthy population with trait paranoia (Savulich et al 2018). We propose that empathy, which produced a qualitatively unique emotional profile under ATD, may represent an important proxy for sensitivity to changes in serotonin.…”
Section: Discussionmentioning
confidence: 95%
“…We employed a novel task, part of the EMOTICOM neuropsychological testing battery (Bland et al 2016;Savulich et al 2018), to measure feelings of guilt, shame, annoyance, and feeling "bad". Using a touchscreen computer, participants were presented with cartoons of social scenarios -Pavlovian cues -in which someone was unjustly harmed, either intentionally or unintentionally.…”
Section: Moral Emotions Taskmentioning
confidence: 99%
“…EMOTICOM (http://www.cambridgecognition.com) is a novel neuropsychological test battery of emotion processing, motivation, impulsivity and social cognition. Recent evidence has shown that this battery is likely to be highly relevant to “hot” cognitive processes in paranoid schizophrenia, as one key aspect implicated in the formation and maintenance of a persecutory delusion is the hostile perception of others, including their beliefs and intentions. EMOTICOM could also be used in treatment development and efficacy research, such as the evaluation of the neuropeptide oxytocin, which has shown some effects on social cognition in schizophrenia.…”
mentioning
confidence: 99%